2020
DOI: 10.1523/jneurosci.0851-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Converging Evidence for Differential Specialization and Plasticity of Language Systems

Abstract: Functional specialization and plasticity are fundamental organizing principles of the brain. Since the mid-1800s, certain cognitive functions have been known to be lateralized, but the provenance and flexibility of hemispheric specialization remain open questions. Language is a uniquely human phenomenon that requires a delicate balance between neural specialization and plasticity, and language learning offers the perfect window to study these principles in the human brain. In the current study, we conducted tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…A large number of neurocognitive studies have since revealed how the dynamics of the language network change after the acquisition of a second language. These empirical findings have suggested that this neuroplastic process permeates both brain structure and function [ 2 , 3 , 6 , 67 ]. This process has also been explored using longitudinal approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of neurocognitive studies have since revealed how the dynamics of the language network change after the acquisition of a second language. These empirical findings have suggested that this neuroplastic process permeates both brain structure and function [ 2 , 3 , 6 , 67 ]. This process has also been explored using longitudinal approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A remarkable feature of the central nervous system is its inherent capacity to dynamically reorganize its structure and function depending on the environment [ 1 , 2 , 3 , 4 , 5 , 6 ]. This capacity for neuroplasticity can give rise to changes in both healthful (e.g., acquisition of a new language; [ 7 , 8 ]) and pathological (e.g., presence of brain lesions; [ 4 , 5 ]) contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Study 2 included participants with proficiency levels varying from basic to advanced as measured by the standardised Quick Placement Test. Gurunandan et al (2020) reported that increasing proficiency of L2 accompanied more divergent lateralization patterns between L1 and L2. This result was not replicated in our study, with participants of all proficiencies showing similar LI strengths across all tasks.…”
Section: Discussionmentioning
confidence: 98%
“…It is worth highlighting that our studies only used expressive language tasks, which typically produce strong lateralisation. Where discrepancies in laterality have previously been reported, this has been for receptive language tasks - both in behavioural contexts (dichotic listening), and in neuroimaging (comprehension or lexical decision tasks) ( Gurunandan et al , 2020 ; Hull & Vaid, 2007 ; Wartenburger et al , 2003 ). It is possible that the processes that drive this effect seen in the literature are not recruited during expressive language production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation